Teachers' Perception on Identity Construction: Lived Experience of Community School Teachers in Nepal (Prithvi Academic Journal, 2022)
This article shows how rural community school teachers use potential resources to construct and negotiate possible teacher identities. Moreover, this article explores how teacher identities can be constructed and understood in the rural society. Five teachers from different disciplines were purposefully selected and interviewed through the semi-structured interview guidelines in a natural setting. The interview responses were transcribed verbatim and analyzed by developing the themes to draw a conclusion. In the teacher’s narratives, themes such as professional ethics and competency, community respect, and societal participation were identified from the discussion of teacher narratives. This article discusses how the negotiation between multiple identities is a crucial part of the teacher identity construction. The findings of this study implicate that rural teachers construct their professional identity with their competency and community participation. It can also contribute to developing values, beliefs and commitments that are emotionally adhered to the teachers' identity construction.